Magnetic resonance imaging is a valuable tool to evaluate the therapeutic efficacy of burosumab in children with X-linked hypophosphatemia. Issue 4 (27th August 2021) - Zhukouskaya, Volha V; Mannes, Inès; Chaussain, Catherine; Kamenický, Peter; Audrain, Christelle; Lambert, Anne-Sophie; Nevoux, Jérôme; Wicart, Philippe; Briot, Karine; Di Rocco, Federico; Trabado, Séverine; Prié, Dominique; et al.
Abstract: Purpose: To examine the MRI diagnostic performance in the assessment of therapeutic response to burosumab in children with X-linked hypophosphatemia (XLH). Design: Prospective longitudinal open cohort. Patients: Seventeen children with XLH, average age of 10.2 ± 2.7 years, had a knee MRI at baseline and after 1 year of burosumab. Intervention: Children received burosumab at an average dose of 1.4 ± 0.5 mg/kg during 1 year for the treatment of severe rickets (the target serum phosphate ≥ 1.2 mmol/L (≥3.7 mg/dL). The primary endpoint was the change from baseline to 12 months in rachitic lesions on knee MRI. Secondary endpoints were changes in biochemical parameters of phosphate and alkaline phosphatase (ALP). Results: One year of treatment with burosumab significantly reduced radiological disease activity on knee MRI (by 44 ± 29% in the transverse extent of widening) which was accompanied by a significant reduction in biochemical activity, namely in serum ALP activity, by 28 ± 17%. Additionally, MRI parameters after 1 year of treatment with burosumab (the maximum width of medial physis at 12 months and the change from baseline in the maximum width of lateral physis) were associated with ALP activity at 12 months. Conclusion: We suggest that MRI is a valuable and quantitative tool to evaluate the therapeutic response to burosumab. MRI could be an excellent alternative to standard bone radiographs for evaluation of the rachitic lesions in a clinical setting avoiding repeated exposition to ionizing radiation.